Impediments to Effective Councilor Oversight at Nkayi Rural District Council in Zimbabwe - Chilunjika, Alouis; Mutema, Edson; Dube, Buhle (International Journal of Law and Public Policy (IJLAPP), 2020)
The paper seeks to examine and unpack the factors that are militating against councilor oversight at Nkayi Rural District Council. Councilor oversight is a crucial function for promoting and enhancing transparency, accountability, effectiveness and efficiency in Zimbabwean local authorities. Despite the existence of councilor oversight, local authorities in Zimbabwe continue to face operational, regulatory and oversight challenges. To establish the factors militating against effective councilor oversight at Nkayi, the respondents were purposively selected and the research used both primary and secondary data. The study established that low academic qualifications among councilors, councilors terms of office, political affiliation and partisanship and limited timeframes as the key impediments to effective councilor oversight at Nkayi Rural District Council.